Generación de los residuos sólidos y el impacto en la salud de los vendedores del mercado Belén 2024 - Guzman Correa, Jose Daniel (2025)
This research aimed to determine the relationship between solid waste generation and its impact on the health of vendors at the Belén Market in 2024. The study was conducted using a quantitative approach, at a relational level, with a non-experimental and cross-sectional design. The population consisted of 2,569 vendors, from which a representative sample of 183 was obtained through stratified sampling with proportional allocation. The independent variable was solid waste generation, measured through direct observation and weighing with a digital scale, while the dependent variable was health impact, assessed through a structured questionnaire validated with a Cronbach’s alpha of 0.796. The results showed that the waste generated inside the market averaged 0.57 kg per stall, while in the exterior area, a significantly higher average of 4.47 kg was recorded. Regarding the health impact, an average score of 68.60 out of 90 was obtained, indicating a moderate level of health affection. The Spearman correlation analysis yielded a coefficient of ρ = -0.251, revealing a weak and statistically significant negative relationship between waste generation and health impact. This correlation suggests that other unmeasured factors may influence the health of the vendors. It is concluded that although there is considerable solid waste generation, its direct relationship with the vendors' health is limited, highlighting the need to consider additional environmental, social, and behavioral variables in future research.